2021
DOI: 10.1111/plb.13307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc application on the growth and photosynthetic characteristics of pecan at the seedling stage

Abstract: Pecan (Carya illinoinensis) is sensitive to Zn, which is involved in basic physiological and biochemical processes.• To explore the growth and physiology of pecan in response to Zn application, we used 1-year-old annual grafted seedlings (Pawnee) and applied four concentrations of Zn fertilizer (0.05, 0.10, 0.20 and 0.40 gÁplant À1 ); a control (CK; no Zn fertilization) was also included. The growth characteristics, anatomical structure of the leaves and photosynthesis were assessed.• Compared with the CK, pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
(58 reference statements)
0
4
1
Order By: Relevance
“…In group C, which was treated with zinc twice, varying zinc concentrations did not significantly influence the photosynthetic parameters of the ginkgo plants. This finding contrasts with a study by Lui et al [47], which suggested that excessive zinc could hinder plant photosynthesis. This discrepancy could be attributed to the possibility that pecans are more susceptible to zinc [48].…”
Section: Discussioncontrasting
confidence: 98%
“…In group C, which was treated with zinc twice, varying zinc concentrations did not significantly influence the photosynthetic parameters of the ginkgo plants. This finding contrasts with a study by Lui et al [47], which suggested that excessive zinc could hinder plant photosynthesis. This discrepancy could be attributed to the possibility that pecans are more susceptible to zinc [48].…”
Section: Discussioncontrasting
confidence: 98%
“…Magnesium is the principal component of the tetrapyrrole ring of chlorophyll molecule [ 89 ], and excess Zn application has been documented to decrease chlorophyll content [ 90 ]. The decreased chlorophyll content reported for S. sclarea plants exposed to 900 μM Zn for 8 days [ 7 ] can be attributed to the decreased Mg content in the aboveground tissues that was observed ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive Zn supply in plants may impair plant growth, disturb chlorophyll synthesis, and induce nutrient imbalances [14,84]. Excess Zn supply (>300 µM) has been reported to reduce chlorophyll [3,14,29,84,85] and either sustain photosynthetic efficiency [84], enhance photosynthetic function [3,14], or restrict it [29]. The reduced chlorophyll in S. sclarea plants that was observed after exposure to 900 µM Zn for 8 days (Figure 3a) could be attributed to Mg decline (Figure 1b).…”
Section: Discussionmentioning
confidence: 95%